Analysis of The Growth of Oil Palm (Elaeis guineensis Jacq.) Exposed by Aluminum Toxicity and Silica as an Amelioration - Satiti Ratnasari; Eka Tarwaca Susila Putra; Didik Indradewa (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Aluminum (Al) contained in acidic soil could become an obstacle for plant growth. The Al toxicity could inhibit root growth, water and nutrient absorption. One of the solution to overcome Al toxicity was by applying Silica (Si). The aim of this research was to study the impacts of Al to the growth activity of oil palm and to know the effects of Si to the growth activity of oil palm contaminated by Al. The factorial treatments were arranged in a complete random design with two factors. The first factor was Al toxicity, i.e. with and without Al, while the second factor was the application of Si that consisted of four levels (0, 32, 64, 96 gram per plant). some of variables included leaf area ratio (LAR), leaf area, net assimilation rate (NAR), relative growth ratio (RGR), plant height, and plant dry weight were observed. The result showed that Al toxicity decreased the LAR, leaf area, NAR, RGR, plant height, and plant dry weight. The application of Si 32 gram per plant increased leaf area ratio and was not significantly different from the application of 96 gram Si per plant. However, the application of Si to oil palm contaminated with Al did not affect to relative grow rate, but its application to normal plant would increase the relative growth ratio.